Challenges Faced by Parents of Children With Speech Disorder in Koto Lamo - Elda Selja Putri; Absharini Kardena (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2022)
Parenting a child is difficult, but parenting disabled children is even more difficult. The complexity of a child's disability needs to be coupled with its complexity, frequently putting parental skills to the test. The experiences of three parents of children with speech disorders disabled children are examined in this study. A phenomenological framework and study strategy were adopted to collect data, including group discussions and individual interviews. The first participant in this study is J, who has a 17-year-old disabled son; the second is SY, who has a 4-year-old disabled son; and the last one is A, who has a 19-year-old disabled daughter. The researchers used content analysis in this study. Per review and member checks were used to improve credibility. The themes that emerged showed that parents had different experiences parenting their children with disabilities, as well as the need to provide parents with accurate information about their children's problems. It seemed clear that such parents would gain from counselling to help them cope with the problematic situations of raising a disabled kid. The author suggests that this study showed the challenges faced by parents who have speech disorders and disabled children, especially in Koto Lamo.